Outsourcing Logistics at Petrol Stations in Slovenia - Zelenika, Ratko; Bečaj, Darko; Pavlić Skender, Helga (Promet - Traffic&Transportation, 2008)
The environmental disburdening by means of outsourcinglogistics (sorting, bundling, transport) is today significantlymore present, since this has been regulated by the law provisionson environmental protection and the economic reasons.Outsourcing logistics in this field with its activities such as: improvementin assembling separate fraction, introduction ofnew, i. e. additional boxes, usage of specific vehicles for collectionand dispatch, reestablishment of information systems andorganization of a centre for disburdening of the environment(sorting, bundling and waste disposal) is contributing largely toa better accomplishment of the mission of logistics rationalizationand adaptation to new law claims on environmental protection.KEYWORDS